EKSPERIMENTASI PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN GROUP INVESTIGATION TERHADAP PRESTASI BELAJAR PERSAMAAN GARIS LURUS DITINJAU DARI KECERDASAN MAJEMUK SISWA KELAS VIII SMP DI KABUPATEN PONOROGO - Jemani, Jemani (Jurnal Pembelajaran Matematika, 2013)
AbstractThis Research aims to find out: (1) which one is better, the learning use Expository, Jigsaw or Group Investigation models to effect mathematics achievement of straight line equation, (2) which one is better, the learning with linguistic intelligence, logical mathematical intelligence or visual spatial intelligence to effect mathematics achievement of straight line equation, (3) for students of multiple intelligences various, which one is better, the learning use Expository, Jigsaw or Group Investigation models to effect mathematics achievement of straight line equation. The research was desained by faktorial 3x3. The research population was VIII grade of Junior High School first semester of 2012/2013 at Ponorogo regency. The sample was taken by using Stratified Cluster Random Sampling, obtained some students of SMP Negeri 6 Kecamatan Ponorogo, SMP Negeri 5 Kecamatan Ponorogo dan SMP Negeri 2 Kecamatan Babadan ordered as high, medium and low groups. The data collection was taken by document, questionnaire dan test method. Document method was used for finding the report scores of VII grade second semester of 2011/2012 academic year, as balance test for GI, Jigsaw and Expository learning. Questionnaire method was used to know the dominance multiple intelligences of students. So, test method was used to know mathematics achievement of straight line equation. Technique of data analizing was used an unbalanced two way analysis of variance. The result of research were: (1) Group Investigation learning and Expository learning have the mathematics achievement of straight line equation better than Jigsaw learning, meanwhile Expository learning have the mathematics achievement of straight line equation same as Group Investigation learning, (2) among student with linguistic intelligence, logical mathematical intelligence or visual spatial intelligence have the same of mathematics achievement of straight line equation, (3) among the students of multiple intelligence, Group Investigation learning and Expository learning to effect mathematics achievement of straight line equation better than Jigsaw learning and Group Investigation learning to effect mathematics achievement the same as Expository learning.Keywords: Group Investigation, Jigsaw, Expository, Multiple Intelligences